CT evaluation of normal bone thickness overlying the superior semicircular canal. (August 2019) - Kaur, Taranjit; Johanis, Michael; Miao, Tyler; Romiyo, Prasanth; Duong, Courtney; Sun, Matthew Z.; Ferraro, Regan; Salamon, Noriko; McArthur, David; Yang, Isaac; Gopen, Quinton
Highlights: Superior semicircular canal dehiscence (SSCD) is an uncommon neurotologic disorder. Healthy patients present an even distribution of bone thickness in the SSC. Lack of association between bone thickness and age or gender. CT scans revealed that 90% of normal patients' bone thickness was 0.40 mm or greater. Abstract: Superior semicircular canal dehiscence (SSCD) is a rare inner ear disorder with variable amounts of auditory and vestibular dysfunction. In addition to the absence of bone overlying the superior semicircular canal, thinning of bone in this area can also initiate the vestibulocochlear symptoms of SSCD. We evaluated normal bone thickness overlying the course of the semicircular canal using computed tomography (CT) scans and assessed correlations between bone thickness and age, gender, and location of the thinnest bone. A single-institution retrospective chart review was conducted on 133 high-resolution CT scans from 76 healthy, asymptomatic patients between ages 9 and 96 years. These CT scans of the temporal bone were obtained between January 2012 and August 2017. The superior semicircular canal dome thickness at the apex was reported with a mean of 1.25 mm for all 76 patients; the 10th percentile was 0.60 mm, and the 90th percentile was 2.08 mm. The thinnest area of bone at any location yielded a mean of 0.86 mm. The normal bone thickness overlying the superior semicircular canal does not depend on gender or age. The thinnest location was evenly distributed across the superior semicircular canal. A bone thickness of 0.40 mm or greater was present in 90% of normal patients based on CT scan measurements at the thinnest location.